Pós-memória como herança: fotografia e testemunho do “retorno” de África - Peralta, Elsa (2017)
This article offers a possible understanding of the “return” of Portuguese-controlled territory to African nations in order to qualify and bear witness to the implications of Portuguese decolonization. In following the story, memory, and their inheritances, we walk toward this event, which we might conventionally describe as one of “the black spots of history—thus reflecting the ethical and analytical value of the concept of recollection and archive in the course of representing other possible paths.